2019
DOI: 10.1002/ange.201908875
|View full text |Cite
|
Sign up to set email alerts
|

A Crystallographic Charge Density Study of the Partial Covalent Nature of Strong N⋅⋅⋅Br Halogen Bonds

Abstract: The covalent nature of strong NÀBr···N halogen bonds in ac ocrystal (2)o fN -bromosuccinimide (NBS)w ith 3,5-dimethylpyridine (lut)w as determined from X-rayc harge density studies and compared to aw eak N À Br···O halogen bond in pure crystalline NBS (1)and acovalent bond in bis(3methylpyridine)bromonium cation (in its perchlorate salt (3). In 2,the donor NÀBr bond is elongated by 0.0954 ,while the Br···acceptor distance of 2.3194(4) is 1.08 shorter than the sum of the van der Waals radii. Amaximum electron d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…These reveal how electron densities in both the donor and the acceptor molecules are ostensibly perturbed by the formation of the halogen bond, primarily about the donor and acceptor atoms (as demonstrated in earlier studies by crystallographic charge density analysis) . By concentrating however on the nonbonding iodine atom, a large increase of electron density can be seen in the σ-hole region of the atom, coupled with a slight decrease of electron density perpendicular to itparticularly visible in the 2:1 complex of 135titfb (Figure ).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…These reveal how electron densities in both the donor and the acceptor molecules are ostensibly perturbed by the formation of the halogen bond, primarily about the donor and acceptor atoms (as demonstrated in earlier studies by crystallographic charge density analysis) . By concentrating however on the nonbonding iodine atom, a large increase of electron density can be seen in the σ-hole region of the atom, coupled with a slight decrease of electron density perpendicular to itparticularly visible in the 2:1 complex of 135titfb (Figure ).…”
Section: Resultsmentioning
confidence: 98%
“…These reveal how electron densities in both the donor and the acceptor molecules are ostensibly perturbed by the formation of the halogen bond, primarily about the donor and acceptor atoms (as demonstrated in earlier studies by crystallographic charge density analysis). 26 By concentrating however on the nonbonding iodine atom, a large increase of electron density can be seen in the σ-hole region of the atom, coupled with a slight decrease of electron density perpendicular to itparticularly visible in the 2:1 complex of 135titfb (Figure 4). Therefore, while there is a significant decrease of the (positive) ESP on the iodine atom, the change of the total charge is slighter, as the corresponding increase of electron density is partially compensated by a slight increase in the perpendicular direction.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although hydrogen bond has remained the “interaction of choice” for the design of supramolecular structures, the research into designing multicomponent systems in which halogen bond acts as the principal intermolecular interaction has been intensifying over the past two decades. This is in part due to the strength and directionality of halogen bonds, which often exceed those of hydrogen bonds and enable the halogen bond to be used as a predictable and robust “binding agent” for planed preparation of desired supramolecular architectures. However, the majority of studies of using halogen bond in supramolecular chemistry have been focused on systems comprising neutral molecules, leaving ionic halogen-bonded structures still somewhat underinvestigated. The majority of ionic halogen-bonded systems studied to date are systems with halogenide anions as acceptors.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that hydrogen bond with the oxygen atom can greatly facilitate this proton transfer in the solid-state by stabilizing the keto-amino form [22][23][24][25][26]. This has led to the question of whether the halogen bond-an interaction in many ways similar to hydrogen bond [27][28][29][30]-can have a similar effect on the intramolecular hydrogen transfer and stabilization of the keto-amino tautomer. Unfortunately, despite the research on halogen bonded o-hydroxyimine systems performed to date [31][32][33][34][35][36][37], the answer to this question remained inconclusive.…”
Section: Introductionmentioning
confidence: 99%